Gadolinium deposition disease: Initial description of a disease that has been around for a while - Semelka, Richard C.; Ramalho, Joana; Vakharia, Ami; AlObaidy, Mamdoh; Burke, Lauren M.; Jay, Michael; Ramalho, Miguel (Magnetic resonance imaging, 2016)
To describe the clinical manifestations of presumed gadolinium toxicity in patients with normal renal function. Participants were recruited from two online gadolinium toxicity support groups. The survey was anonymous and individuals were instructed to respond to the survey only if they had evidence of normal renal function, evidence of gadolinium in their system beyond 30days of this MRI, and no pre-existent clinical symptoms and/or signs of this type. 42 subjects responded to the survey (age: 28–69, mean 49.1±22.4years). The most common findings were: central pain (n=15), peripheral pain (n=26), headache (n=28), and bone pain (n=26). Only subjects with distal leg and arm distribution described skin thickening (n=22). Clouded mentation and headache were the symptoms described as persistent beyond 3months in 29 subjects. Residual disease was present in all patients. Twenty-eight patients described symptoms following administration of one brand of Gadolinium-Based Contrast Agent (GBCA), 21 after a single GBCA administration and 7 after multiple GBCA administrations, including: gadopentetate dimeglumine, n=9; gadodiamide, n=4; gadoversetamide, n=4; gadobenate dimeglumine, n=4; gadobutrol, n=1; gadoteridol, n=2; and unknown, n=4. Gadolinium toxicity appears to arise following GBCA administration, which appears to contain clinical features seen in Nephrogenic Systemic Fibrosis, but also features not observed in that condition.